A CASE OF A LYME DISEASE IN THE SECOND TRIMESTER OF PREGNANCY - Ana Kocevska; Anamarija Shpishikj Pushevska; Pranvera Izairi; Arta Islami Zulfiu; Bekim Dika; Iskra Martinovska (Македонско лекарско друштво = Macedonian medical association, 2025)
Introduction: Lyme disease is the most common tick-borne disease in North America and Europe and it is caused by spirochetal bacteria Borelia burgdorferi. Early symptoms of infection include a characteristic rash (erythema migrans), fever, headache and lethargy. If untreated, the disease may affect the heart, nervous system and joints. Regardless of whether maternal exposure to B. burgdorferi occurs before conception or during pregnancy, it does not appear to be associated with fetal death, prematurity or risk of congenital malformations. Even documented infection of the placenta with B. burgdorferi has not been linked to adverse pregnancy outcomes. Also, there have been no reported cases of transmission of B. burgdorferi via breast milk. Antibiotics used during pregnancy are amoxicillin or cephalosporins, 14-21 days. Case report: A 24-year-old primigravida, at 23 weeks of gestation, reported that 3 weeks earlier she had been bitten by a tick that had not been removed by a surgeon. A change appeared as a red ring of about 10 cm in the gluteal region on the right, as well as joint pain, without fever. She was examined by an infectious disease specialist. Serological tests were performed and a high titer of IgG and IgM antibodies for Borelia burgdorferi sensu lato were detected. Antibiotic therapy Amp. Ceftriaxone 2gr/day was administered for 14 days, which prevented further complications in mother or fetus. Conclusion: With this case, we want to point out that Lyme borreliosis is present, that a tick bite is serious and requires an examination by a surgeon and an infectious disease specialist, in order to properly remove the tick and prevent the occurrence of this disease, which is possible even during pregnancy. It is also important to be aware of its symptoms, in order to start antibiotic therapy before more serious complications arise.
Keywords: Lyme disease; tick-born disease; Borelia burgdorferi; erythema migrans